Roots of theological anti-Semitism German biblical interpretation and the Jews, from Herder and Semler to Kittel and Bultmann - Gerdmar, Anders (Leiden ; Boston : Brill, 2009)
As Adolf Hitler strategised his way to power, he knew that it was necessary to gain the support of theology and the Church. This study looks at roots of theological anti-Semitism and how Jews and Judaism were constructed, positively and negatively, in the biblical interpretation of German Protestant theology.
Foreword; Introduction: Roots of Theological Anti-Semitism; PART I ENLIGHTENMENT EXEGESIS AND THE JEWS; Introduction; The Jews in Enlightenment Exegesis From Deism to de Wette; Johann Salomo Semler: Dejudaising Christianity; Johann Gottfried Herder: The Volk Concept and the Jews; F.D.E. Schleiermacher: Enlightenment Religion and Judaism; W.M.L. de Wette: Judaism as Degenerated Hebraism; The Jews in Enlightenment Exegesis from Baur to Ritschl; Ferdinand Christian Baur: Judaism as an Historical Antipode of Christianity.
Includes bibliographical references (pages 619-651) and indexes.
Print version record.
Keywords: Bible -- Criticism, interpretation, etc. -- History; Bible; Neues Testament; Judaism (Christian theology) -- History of doctrines; Christianity and antisemitism -- Germany -- History; Christianity and other religions -- Judaism -- History; Judaism -- Relations -- Christianity -- History; Theology, Doctrinal -- Germany -- History; Antisemitism -- Germany -- History; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Antisemitism; Christianity; Christianity and antisemitism; Interfaith relations; Judaism; Judaism (Christian theology) -- History of doctrines; Theology, Doctrinal; Germany; Antisemitismus; Theologie; Exegese; Antijudaismus; Deutschland; Antijudaismus; Antisemitismus; Bibelwissenschaft; Exegese; Juden; Judentum; Protestantismus; Deutschland; Geschichte 1750-1950.; Geschichte; Electronic books; Criticism, interpretation, etc; History